Romania’s EU Accession Negotiations: the Significance of the EU Budget - Robert Ackrill (Romanian Journal of European Affairs, 2005)
Romania completed its negotiations for accession to the European Union, as scheduled, by the end of 2004. The experience of the negotiations over the 2004 enlargement confirmed that the EU budget is an absolutely key issue in such talks. The purpose of this paper is to consider the context of Romania’s negotiations over the EU Budget. First, we look at the relationship the EU15 member states have with the EU budget. We show how rules governing the operation of the EU Budget have affected budgetary flows to the EU15 and highlight the stability over time of the shares of total budget flows to and from each member state. Second, we look at the experience of the new Member States in their accession negotiations and review the outcomes. This will allow us to see how the political economy of the EU Budget affected the talks and the deal the new member states were able to secure. We then apply the lessons learned to the case of Romania. Our analysis reveals inflexibilities in the negotiations that left Romania more or less facing a ‘take-it-or leave- it’ offer.